A variety of interface and strain tuning electronic properties of the MoS2/Cr2CX2 van der Waals heterostructures. (11th June 2021) - Sun, Qian; Li, Yi; Yang, Zongxian
Abstract: Two-dimensional transition metal carbide Cr2 C is a potential magnetic material with controllable magnetic properties. The structures of MoS2 and Cr2 CX2 (X = O, F, OH) are similar, and the lattice constants are about the same. The present work addresses interfaces between the nonmagnetic semiconductor MoS2 and the ferromagnetic metal Cr2 C and Cr2 CO2, as well as the antiferromagnetic semiconductor Cr2 CX2 (X = F and OH), to explore the potential of these new hybrid systems in all-2D electronic and optoelectronic devices. The electronic structure of the van der Waals heterostructures composed of the MoS2 and Cr2 CX2 monolayers is studied using first-principles method. Our results show that the electronic structure of the MoS2 /Cr2 CX2 heterostructures with different functional groups is very different. While MoS2 /Cr2 C and MoS2 /Cr2 CO2 are metals, MoS2 /Cr2 CF2 and MoS2 /Cr2 C(OH)2 are semiconductors. Biaxial strain applied to the heterostructures of MoS2 /Cr2 CF2 and MoS2 /Cr2 C(OH)2 makes their band gap decreasing and even causes a phase transition from semiconductor to metal. The results indicate that the MoS2 /Cr2 CX2 heterostructures can have tunable electronic and magnetic properties with different functional groups introduced or strain applied, which would have potential applications in designing high-performance electronic devices.